The Impact of Higher Order Thinking Skills (HOTS) Instructions in Teaching EFL Speaking Skill from the Perspective of Students’ Motivation - Yuniarta Ita Purnama; Fitri Nurdianingsih (Lingua Cultura, 2019)
The purpose of the research was to examine (1) whether or not the HOTS instruction was more effective than the LOTS (Lower Order Thinking Skills) instruction in teaching speaking for daily context to the first semester students at English Education department; (2) whether the students who had high self-motivation had better speaking ability than those who had low self-motivation; and (3) whether there was an interaction between teaching strategies and students’ self-motivation. By using a quantitative research with the quasi-experimental type, the data were derived from tests and questionnaires. The results show that (1) HOTS instruction is more effective than the LOTS instruction in teaching speaking for daily context to the first semester students at the English Education Department; (2) the students who have high motivation have better speaking skills than the students who have low motivation; (3) there is an interaction between teaching strategies and motivation in teaching speaking for daily context. It can be concluded that HOTS instruction is an effective strategy in teaching speaking viewed from students’ motivation. The effectiveness of the strategy is affected by students’ motivation.